MAKNA DAN FUNGSI TEMBANG DANG-DANG DALAM PERNIKAHAN ADAT ISTIADAT MASYARAKAT DESA BANYU URIP KECAMATAN PRAYA BARAT KABUPATEN LOMBOK TENGAH PROVINSI NUSA TENGGARA BARAT - Rachmasari, Annisa Debby; Yuliana, Baiq Tety; Qurani, Fitrahtullah Oktarina Nurul (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2018)
This study aims to determine the meaning contained in Tembang Dang-dang and to know the functions contained therein. This study uses a semiotic approach proposed by Roland Barthes and the functional approach proposed by David Kaplan and Albert Manners. The method used is content analysis method. The source of data used is Adat Pemangku named Mamiq Taufan, he is the only Pemangku Adat in Banyu Urip Village, West Praya Subdistrict, Central Lombok Regency, NTB. Data on Tembang Dang-dang is also obtained from Mamiq Taufan because only he knows the ins and outs of the birth of Tembang Dang-dang. Data collection techniques used by researchers in analyzing Tembang Dang-dang by Sunan Bonang is document study and interview to informant. The final result of this research is the first meaning of denotation and connotation in Tembang Dang-dang. Then the second there are several functions namely religious function, social function and cultural function.